2017
DOI: 10.2196/jmir.8481
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Telephone-Based eHealth Literacy Scale Among Older Adults: Cross-Sectional Survey

Abstract: BackgroundOnly a handful of studies have examined reliability and validity evidence of scores produced by the 8-item eHealth literacy Scale (eHEALS) among older adults. Older adults are generally more comfortable responding to survey items when asked by a real person rather than by completing self-administered paper-and-pencil or online questionnaires. However, no studies have explored the psychometrics of this scale when administered to older adults over the telephone.ObjectiveThe objective of our study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
65
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 45 publications
11
65
3
Order By: Relevance
“…Sudbury-Riley and colleagues [39] also found that a 3-factor model of information awareness, seeking, and appraisal skills among baby boomers and older adults from European and North American nations. Consistent with these studies, a 3-factor model has also been confirmed among baby boomers and older adults [36], including chronic disease patients [34] and adults, with an average age of 53, in a magnetic resonance imaging and computed tomography medical imaging outpatient clinic [40]. Despite evidence for measurement invariance among middle-to-older age adults in multiple nations [39], empirical attention is needed to confirm the 3-factor structure among a general population consisting of younger and older adults.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…Sudbury-Riley and colleagues [39] also found that a 3-factor model of information awareness, seeking, and appraisal skills among baby boomers and older adults from European and North American nations. Consistent with these studies, a 3-factor model has also been confirmed among baby boomers and older adults [36], including chronic disease patients [34] and adults, with an average age of 53, in a magnetic resonance imaging and computed tomography medical imaging outpatient clinic [40]. Despite evidence for measurement invariance among middle-to-older age adults in multiple nations [39], empirical attention is needed to confirm the 3-factor structure among a general population consisting of younger and older adults.…”
Section: Introductionsupporting
confidence: 77%
“…The Mdn age value of the current sample was 49, and an inspection of a histogram showed a bimodal age distribution. Consistent with principles of SEM and the average age value in existing exploratory eHEALS measurement studies [ [34][35][36]39], using age 49 as a cut-off value was appropriate to create two age groups: young and old . Frequency and descriptive statistics were computed to describe the sample and eHealth literacy scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the Internet use among older people is steadily increasing, as they search and visit websites for on-line health information and discussion. 34 There has been a tremendous development on the Internet front since the original eHEALS was designed 15 years ago, and, as Stellefson et al 34 point out, it is important to consider modifying the scale to better fit the relevance for use among an older population.…”
Section: Discussionmentioning
confidence: 99%